Hoarseness among nurses - Vilén Liisa; Putus Tuula (Mosby Inc., 2022)
While many occupations are at risk for vocal health issues much of the current research has focused on teachers. The prevalence of hoarseness among nurses has not received much attention. The aim of this study was to determine the current prevalence of hoarseness among nurses and also to identify potential environmental risk factors from their working environment. The health data was collected from Finnish healthcare workers. Our findings are based on 13,560 health questionnaires which were statistically analyzed. Our results suggest that the one-year period prevalence of hoarseness was 30% and all the environmental problems which we evaluated (draft, room temperature too high, variable room temperature, room temperature too low, dry air, stuffy indoor air, moist air/ high humidity, inadequate ventilation, smell of mold or cellar, sewer odor, other unpleasant odors, tobacco smoke, noise and detectable dust or dirt) had an increasing effect on hoarseness. In conclusion, clear associations were found between environmental problems and hoarseness in nurses. Furthermore, efforts should be made to repair defective ventilation systems, remediate indoor air problems due to moisture damage and improve overall maintenance to protect the vocal health of nurses.